2002
DOI: 10.1148/radiol.2231010234
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty for Severe Osteoporotic Vertebral Body Compression Fractures

Abstract: Percutaneous vertebroplasty for severe osteoporotic vertebral body compression fractures is safe and effective and should not be withheld in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
1
12

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(141 citation statements)
references
References 12 publications
7
119
1
12
Order By: Relevance
“…However, as it proved successful with these lesions, the indications also expanded to include osteoporotic compression fractures refractory to medical treatment. The initial experience with vertebroplasty for the treatment of osteoporotic fractures has shown 70-95% pain relief [3, 13,15,18,22,23,26,28,29,31,33,46,50,51,61]. The mechanism by which PVP achieves its palliative effect is not known.…”
Section: Introductionmentioning
confidence: 99%
“…However, as it proved successful with these lesions, the indications also expanded to include osteoporotic compression fractures refractory to medical treatment. The initial experience with vertebroplasty for the treatment of osteoporotic fractures has shown 70-95% pain relief [3, 13,15,18,22,23,26,28,29,31,33,46,50,51,61]. The mechanism by which PVP achieves its palliative effect is not known.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Specific clinical and imaging selection criteria include duration and pattern of subjective pain; imaging characteristics on plain film, MR imaging, and CT; and findings on physical examination. Among these selection criteria, duration of pain has garnered substantial interest.…”
mentioning
confidence: 99%
“…Although many large prospective studies demonstrating the efficacy of vertebroplasty in the treatment of benign vertebral compression fractures have been published, 1,4,5,[7][8][9][10][11][12][13][14][15][16] the data supporting its use in the treatment of compression fractures in patients with multiple myeloma remain limited. Several small studies and case series have demonstrated a beneficial effect, 1,2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] but the largest sample size is composed of only 18 patients.…”
mentioning
confidence: 99%